Chebet Maikut (Uganda) talks on support to the African Group of Negotiators in the UNFCCC - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Interview with Chebet Maikut, Deputy Coordinator - Climate Change Unit in Uganda. He highlights some of the challenges faced by the African Group of Negotiators (AGN) involved in the UNFCCC process and how a number of partners are helping them overcome the same.